Hasil Belajar Siswa melalui Penerapan Model Problem Based Learning di MIN 9 Banda Aceh - Hasanah, Uswatun; Jarmita, Nida; Lubis, Silvia Sandi Wisuda; Nelliraharti, Nelliraharti (Mitra PGMI: Jurnal Kependidikan MI, 2023)
In the Mathematics curriculum, the subject of circles is considered one of the challenging topics for students. Many students struggle with the application in daily life. One effort to address this is by implementing the Problem-Based Learning model in learning process. The aim of this study is to determine the learning outcomes of students through the Problem-Based Learning model, specifically in the subject of circles. This type of research is experimental. The learning outcome obtained through the Problem-Based Learning model wascompared to the mathematics KKM (Minimum Graduation Standard) score in the school, which was 80. The population in this research was all sixth-grade students of MIN 9 Banda Aceh, and the sample was 25 sixth-grade students randomly selected. The instrument used in this research was a test. Based on the evaluation results at the last meeting, the average student score was 87,1 with a standard deviation of 8,30. In the hypothesis testing, a right-sided t-test was used, with a significant level of α = 0,05. The calculation results showed that the implementation of the Problem-Based Learning model in the circle subjectin the sixth grade of MIN 9 Banda Aceh exceeds the KKM.